The evasive text : Zechariah 1-8 and the frustrated reader - Love, Mark Cameron (Journal for the study of the Old Testament. Supplement series ;, 1999)
This work employs an eclectic mix of structuralist and post-structuralist theories in a doomed attempt to discover the symbolic logic at work in Zechariah 1-8's surreal narrative world. Lengthy analyses of Zechariah's intra- and intertextual logic, or lack thereof, are presented. It is finally concluded that Zechariah lacks a concrete symbolic logic, defies grammatical conventions and is 'unreadable' as it stands-and always was this way. One suggestion is that it was the intent of the author, conceived of in a postmodern way, to produce such a work. It is finally concluded that the 'post-proph.